Information monitor method of RFID system based on logarithm spectrum RF fingerprint identification - Hong-lin YUAN; Zhi-hua BAO; Yan YAN (Tongxin xuebao)
To make up for the shortcomings of the information control in RFID systems, an information monitor method of passive RFID systems based on emitter identification was proposed. The emitted RF signal of the passive RFID tag was acquired and transformed into logarithm spectrum RF fingerprint, the features were extracted and classified, and the authenticity of the tag was obtained, the application layer protocol of the reader was integrated with the RF fingerprint etc., and the control of the information between the tag and reader was achieved. It was demonstrated with modeling, simulation and experiments that the novel fingerprint was solely determined by the frequency offset and impulse response of the tag, and had stability etc., a challenge-response authentication protocol instance of RFID systems integrated with the proposed fingerprint was given. The proposed method can not only enhance the authentication intensity, but also monitor the identity of the tag in the communication, and has certain contribution to solve the open question of the secret key leakage detection.